High-performance In-SnO2 / Pd sensitive film for MEMS gas sensor, synthesis method of high-performance In-SnO2 / Pd sensitive film and MEMS gas sensor

Through indium doping and palladium modification of In-SnO2/Pd sensitive film, the problem of detecting gas lower limit height of a single tin dioxide sensitive material is solved, and the sensitivity and response performance of gas detection are significantly improved.

CN119265551APending Publication Date: 2025-01-07HUAZHONG UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411333922.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the prior art, a single tin dioxide is used as a sensitive material for a gas sensor, and the detection gas has a high lower limit and a weak response degree, resulting in a low sensitivity to gas detection.

Method used

In-SnO2/Pd sensitive film is used to generate In3+ doped tin dioxide nanoparticle spheres by indium salt doping, and palladium nanoparticles are modified by solution method to form In3+ doped tin dioxide nanoparticle spheres with Pd modification. , improve gas transmission capacity and oxidation reaction speed.

Benefits of technology

It improves the sensitivity and response performance of gas detection, enhances the adsorption ability to gas, and significantly improves the detection ability of gas concentration changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265551A_ABST
    Figure CN119265551A_ABST
Patent Text Reader

Abstract

The invention belongs to the related technical field of detection sensitive materials, and discloses a high-performance In-SnO2 / Pd sensitive film for an MEMS (Micro Electro Mechanical System) gas sensor, a synthesis method of the high-performance In-SnO2 / Pd sensitive film and the MEMS gas sensor, the method comprises the following steps: S1, uniformly mixing and stirring indium salt, tin salt, hydrochloric acid, ethanol and deionized water, and then carrying out hydrothermal reaction, centrifuging, washing and drying a product of the hydrothermal reaction, and then carrying out first annealing treatment in an air atmosphere to obtain In < 3 + >-doped tin dioxide nanoparticle spheres In-SnO2 which have hollow structures; s2, palladium nanoparticles are modified by the nanoparticle balls In-SnO2 through a solution method, after centrifugation, washing and drying are conducted, secondary annealing treatment is conducted in the hydrogen atmosphere, and In < 3 + >-doped and Pd-modified tin dioxide nanoparticle balls In-SnO2 / Pd are obtained; and S3, preparing the sensitive thin film from the nano-particle spheres In-SnO2 / Pd. According to the sensitive film prepared by the method, the sensitivity to gas detection can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field related to detecting sensitive materials, and more specifically, relates to a high-performance In-SnO2 / Pd sensitive film for a MEMS gas sensor, a synthesis method thereof, and a MEMS gas sensor. Background Art

[0002] Semiconductor gas sensors detect the composition or concentration of gas by using the change in resistance of semiconductor sensitive materials when they come into contact with gas. The gas undergoes an oxidation-reduction reaction with the sensitive material, causing the resistance of the sensitive material to change. Gas detection is achieved by detecting the change in resistance.

[0003] Tin dioxide (SnO2) is an important n-type semiconductor sensitive material, which can be used to detect volatile organic compounds (VOCs) gas, especially in the detection of H2S, and has high potential value. Therefore, SnO2 is currently commonly used as a semiconductor sensitive material for gas sensors.

[0004] However, when using single tin dioxide as a sensitive material, the lower limit of gas detection is high, and it is difficult to trigger a response when the gas concentration is low, or the response is weak, that is, the sensitivity of gas detection is low. Summary of the invention

[0005] In view of the above defects or improvement needs of the prior art, the present invention provides a high-performance In-SnO2 / Pd sensitive film for a MEMS gas sensor, a synthesis method thereof, and a MEMS gas sensor, the purpose of which is to improve the sensitivity of gas detection.

[0006] To achieve the above object, the present invention provides a method for synthesizing a high-performance In-SnO2 / Pd sensitive film for a MEMS gas sensor, which comprises:

[0007] Step S1: firstly, indium salt, tin salt, hydrochloric acid, ethanol and deionized water are mixed and stirred uniformly, and then a hydrothermal reaction is carried out. Then, the product of the hydrothermal reaction is centrifuged, washed and dried, and then a first annealing treatment is carried out in an air atmosphere to obtain In 3+ Doped tin dioxide nanoparticle spheres In-SnO2, wherein the nanoparticle spheres In-SnO2 have a hollow structure;

[0008] Step S2: modifying the nanoparticles In-SnO2 with palladium nanoparticles by a solution method, centrifuging, washing and drying, and then performing a second annealing treatment in a hydrogen atmosphere to obtain In 3+ Doped and Pd-modified tin dioxide nanoparticle spheres In-SnO2 / Pd;

[0009] Step S3: making the nanoparticle balls In-SnO2 / Pd into the sensitive film.

[0010] In an optional embodiment, in step S1, the mixing ratio of the tin salt, hydrochloric acid, ethanol and deionized water satisfies:

[0011] (2.0~2.4)mmol tin atom: (0.6~1.0)ml 35% hydrochloric acid: (48~52)ml ethanol: (4~6)ml deionized water.

[0012] In an optional embodiment, in step S1, the indium salt includes one or more of indium nitrate, indium chloride, and indium acetate, and the tin salt includes one or more of tin nitrate, tin chloride, stannous chloride, and tin acetate.

[0013] In an optional embodiment, in step S1, the ratio of indium salt to tin salt satisfies: the ratio of the number of indium atoms to that of tin atoms is in the range of 1% to 7%.

[0014] In an optional embodiment, in step S1, the ratio of indium salt to tin salt satisfies: the ratio of the number of indium atoms to that of tin atoms is in the range of 3% to 5%.

[0015] In an optional embodiment, in step S2, the step of modifying the nanoparticle spheres with In-SnO2 using a solution method comprises:

[0016] The nanoparticle ball In-SnO2, palladium salt, palladium salt reducing agent and deionized water are mixed evenly. The palladium salt reducing agent is used to reduce the high-valent palladium ions in the palladium salt into a single palladium substance and embed it in the nanoparticle ball In-SnO2. In the nanoparticle ball In-SnO2 / Pd, the ratio of the number of palladium and tin atoms ranges from 0.1% to 5%.

[0017] In an optional embodiment, the annealing temperature of the first annealing treatment is 450°C to 550°C; the annealing temperature of the second annealing treatment is 250°C to 350°C.

[0018] In an optional embodiment, in step S3, the step of making the nanoparticle balls In-SnO2 / Pd into the sensitive film comprises:

[0019] The nano particle sphere In-SnO2 / Pd is made into the sensitive film through a gas / liquid interface self-assembly method.

[0020] The present invention also provides a high-performance In-SnO2 / Pd sensitive film for a MEMS gas sensor, wherein the sensitive film is made of nanoparticle balls In-SnO2 / Pd, wherein the nanoparticle balls In-SnO2 / Pd are In 3+Doped and Pd-modified SnO2 nanoparticle spheres.

[0021] The present invention also provides a MEMS gas sensor, comprising the high-performance In-SnO2 / Pd sensitive film as described above.

[0022] In general, compared with the prior art, the above technical solutions conceived by the present invention mainly have the following beneficial effects:

[0023] 1. The high-performance In-SnO2 / Pd sensitive film synthesis method for MEMS gas sensors proposed in the present invention comprises the following steps: first, indium salt, tin salt, hydrochloric acid, ethanol and deionized water are mixed and stirred evenly, and then a hydrothermal reaction is performed. This step can generate tin dioxide nanoparticles, and due to the addition of indium salt, indium ions will replace part of the tin in the tin dioxide lattice, thereby achieving In 3+ Doping to obtain nanoparticles In-SnO2, In 3+ Doping causes lattice distortion, and the tin dioxide nanoparticles have a hollow structure, thereby growing more oxygen vacancies, which can effectively promote gas diffusion and improve gas transmission capacity. The stronger the gas transmission capacity, the higher the utilization rate of the gas that reacts with the sensitive material, and the higher the sensitivity to gas detection; moreover, oxygen vacancies can act as electron donors, increase the charge density in the band structure, thereby improving the adsorption capacity of gas, and further improving the sensitivity to gas detection. Then, the nanoparticles In-SnO2 are modified with palladium to obtain nanoparticles In-SnO2 / Pd. Pd nanoparticles can modify the surface of SnO2 balls to achieve chemical sensitization and electronic sensitization. Chemical sensitization uses the catalytic properties of Pd nanoparticles to increase the oxidation reaction rate of gas and sensitive film, thereby improving the effectiveness of gas detection. Electronic sensitization uses the fact that Pd nanoparticles can also undergo different degrees of oxidation reactions according to different gas atmospheres, thereby affecting the resistance of the sensitive film, and further improving the sensitivity to gas detection.

[0024] 2. The sensitive film for MEMS gas sensing and the MEMS gas sensor made of the sensitive film mentioned in the present invention are made of nanoparticle balls In-SnO2 / Pd, and the nanoparticle balls In-SnO2 / Pd are In 3+ The doped and Pd-modified SnO2 nanoparticles have In 3+ Doping and Pd modification result in more oxygen vacancies in the nanoparticle spheres and achieve chemical sensitization and electronic sensitization, thereby improving the sensitivity of gas detection.

[0025] 3. In some embodiments, by adjusting the ratio of tin salt, hydrochloric acid, ethanol and deionized water, the size of the synthesized nanoparticle spheres is made more uniform, so that the gas dynamic response of the manufactured sensor has good consistency.

[0026] 4. In some embodiments, by adjusting the ratio of the number of indium and tin atoms, the gas dynamic response of the manufactured sensor can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a flow chart of the steps of a method for synthesizing a high-performance In-SnO2 / Pd sensitive thin film for a MEMS gas sensor in one embodiment of the present invention;

[0028] FIG2( a ) is a SEM image of SnO2 nanoparticle spheres with uneven size distribution obtained in one embodiment;

[0029] FIG2( b ) is a SEM image of SnO2 nanoparticle spheres with uniform size distribution obtained in one embodiment;

[0030] Figure 3 is a composition mapping diagram of the nanoparticle sphere In-SnO2 / Pd in ​​one embodiment of the present invention;

[0031] Figure 4 TEM comparison images of different nanoparticle spheres in one embodiment, wherein (a) corresponds to a pure SnO2 nanoparticle sphere, (b) corresponds to a nanoparticle sphere In-SnO2, (c) corresponds to a nanoparticle sphere In-SnO2 / Pd, and (d) is an enlarged view of (c);

[0032] FIG5(a) is a graph showing the gas response to H2S at different temperatures when different nanomaterials are used as the sensitive film of the MEMS sensor;

[0033] FIG5( b ) is a comparison of gas responses when different nanomaterials are used as sensitive films;

[0034] Figure 5(c) is a graph showing the relationship between gas response and concentration when In-SnO2 / Pd nanomaterials are used as sensitive films;

[0035] FIG. 6( a ) is a SEM image of an 8-inch wafer-level film formed using In-SnO 2 / Pd nanomaterial as a sensitive film in one embodiment of the present invention;

[0036] FIG6( b ) is a diagram showing the consistency test results of the MEMS gas dynamic response of four sensors in four areas on the 8-inch wafer in FIG6( a ) to H2S at 280°C. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0038] The present invention provides a method for synthesizing a high-performance In-SnO2 / Pd sensitive thin film for a MEMS gas sensor. Figure 1 The figure shows a flow chart of the steps of a method for synthesizing a high-performance In-SnO2 / Pd sensitive film for a MEMS gas sensor in one embodiment of the present invention. The method comprises steps S1 to S3, and the steps are introduced below.

[0039] Step S1: First, indium salt, tin salt, hydrochloric acid, ethanol and deionized water are mixed and stirred uniformly, and then a hydrothermal reaction is performed. Then, the product of the hydrothermal reaction is centrifuged, washed and dried, and then a first annealing treatment is performed in an air atmosphere to obtain In 3+ Doped tin dioxide nanoparticle sphere In-SnO2, the nanoparticle sphere In-SnO2 has a hollow structure.

[0040] Specifically, a tin salt, hydrochloric acid, ethanol and deionized water are mixed and reacted to generate SnO2 nanoparticles. The tin salt can be selected from one or more of tin nitrate, tin chloride, stannous chloride and tin acetate.

[0041] In specific operations, the size and morphology of the nanoparticles can be controlled by adjusting the composition ratio of tin salt, hydrochloric acid, ethanol and deionized water. In a preferred embodiment, the composition ratio of tin salt, hydrochloric acid, ethanol and deionized water satisfies: (2.0-2.4) mmol tin atoms: (0.6-1.0) ml 35% hydrochloric acid: (48-52) ml ethanol: (4-6) ml deionized water. Under this composition ratio, the size distribution of the obtained SnO2 nanoparticles is more uniform. Figure 2a The SEM image of SnO2 nanoparticles obtained in the ratio of 2.28mmol SnCl4: 0.8ml 35% hydrochloric acid: 50ml ethanol: 20ml deionized water is shown. Figure 2b Shown is the SEM image of the SnO2 nanoparticle ball obtained in the ratio of 2.28mmol SnCl4: 0.8ml 35% hydrochloric acid: 50ml ethanol: 5ml deionized water. By comparison, it can be seen that by adjusting the ratio, the size distribution of the SnO2 nanoparticle ball can be adjusted, making the size distribution of the SnO2 nanoparticle ball more uniform, which is beneficial to improving the consistency of the sensor's dynamic response to gas.

[0042] In a specific operation, after mixing indium salt, tin salt, hydrochloric acid, ethanol and deionized water, magnetic stirring can be performed for several hours to fully dissolve and mix the components, and then the mixture is transferred to a reactor, and then a hydrothermal reaction is performed to fully react the components. The temperature of the hydrothermal reaction is selected to be 180°C to 220°C, for example, 200°C, and the reaction time can be, for example, 12 hours. In the present invention, due to the addition of indium salt, indium ions will replace part of the tin in the tin dioxide lattice, achieving In 3+ Doping to obtain nanoparticles In-SnO2, In 3+ Doping causes lattice distortion, and the tin dioxide nanoparticles have a hollow structure, thereby growing more oxygen vacancies. The increase in oxygen vacancies enhances the ability to transmit and adsorb gases, thereby improving the sensitivity of gas detection and the response performance of the gas sensor. Specifically, the indium salt can be selected from one or more of indium nitrate, indium chloride, and indium acetate.

[0043] After the hydrothermal reaction, the hydrothermal product is centrifuged, washed and dried, and subjected to a first annealing heat treatment in an air atmosphere. By performing the annealing treatment in an air atmosphere, the nanoparticle spheres can be crystallized to obtain In 3+ Doped tin dioxide nanoparticle ball In-SnO2. In a specific embodiment, the annealing temperature of the first annealing heat treatment can be selected from 450°C to 550°C, and the annealing time can be selected from 1.5h to 2.5h. For example, annealing at 500°C for 2h can be selected to obtain the nanoparticle ball In-SnO2.

[0044] Step S2: In-SnO2 nanoparticles are modified with palladium nanoparticles by a solution method, and then centrifuged, washed and dried, and then annealed for the second time in a hydrogen atmosphere to obtain In 3+ Doped and Pd-modified tin dioxide nanoparticle spheres In-SnO2 / Pd.

[0045] Specifically, the nanoparticle ball In-SnO2, palladium salt, palladium salt reducing agent and deionized water can be evenly mixed, and the palladium salt reducing agent can reduce the high-valent palladium ions in the palladium salt into a single palladium substance and embed it in the nanoparticle ball In-SnO2. In actual operation, the content of palladium atoms can be flexibly adjusted to adjust the response characteristics of the sensor. For example, in the nanoparticle ball In-SnO2 / Pd, the ratio of the number of palladium and tin atoms ranges from 0.1% to 5%. In one embodiment, the palladium salt can be selected from one or more of dichlorotetraamminepalladium, palladium nitrate and palladium chloride, and the palladium salt reducing agent generally selects sodium borohydride. In this embodiment, the palladium salt selects dichlorotetraamminepalladium, and specifically, its ratio can be 0.1g nanoparticle ball In-SnO2 / Pd: 0.005g dichlorotetraamminepalladium: 0.1g sodium borohydride: 10ml of deionized water.

[0046] After the reaction occurs, the second annealing treatment is performed in a hydrogen atmosphere by centrifugation, washing and drying. The oxidized Pd can be reduced to zero-valent Pd particles by annealing in a hydrogen atmosphere and the oxygen vacancy concentration can be further increased, thereby obtaining Pd-modified tin dioxide nanoparticles In-SnO2 / Pd. In a specific embodiment, the annealing temperature of the second annealing heat treatment can be selected from 250°C to 350°C, and the annealing time can be selected from 1.5h to 2.5h. For example, annealing at 300°C for 2h can be selected to obtain nanoparticles In-SnO2 / Pd.

[0047] like Figure 3 The figure shows a composition mapping diagram of the nanoparticle sphere In-SnO2 / Pd in ​​one embodiment. It can be seen from the figure that the nanoparticle sphere In-SnO2 / Pd contains Sn, O, In, and Pd, indicating that In and Pd are successfully added to the SnO2 nanoparticle sphere.

[0048] like Figure 4 The TEM comparison diagrams of different nanoparticle balls in one embodiment are shown, wherein (a) corresponds to a pure SnO2 nanoparticle ball, (b) corresponds to a nanoparticle ball In-SnO2, (c) corresponds to a nanoparticle ball In-SnO2 / Pd, and (d) is an enlarged diagram of (c). It can be clearly seen from the figure that the pure SnO2 nanoparticle ball in (a) is a solid nanoparticle ball, the nanoparticle ball In-SnO2 in (b) has a unique hollow structure, and the nanoparticle ball In-SnO2 / Pd in ​​(c) has Pd added to the nanoparticle ball In-SnO2.

[0049] Step S3: Make the nanoparticle balls In-SnO2 / Pd into a sensitive film.

[0050] In a preferred embodiment, the nanoparticle spheres In-SnO2 / Pd can be made into a sensitive film by air / water interface self-assembly method, and the specific operation is as follows:

[0051] The nanoparticle balls are first treated with dodecyl for hydrophobicization, and then prepared into an ethanol dispersion of In-SnO2 / Pd nanoparticle balls. Finally, the dispersion is dripped drop by drop on the inner wall of a beaker containing deionized water, and finally a single-layer nanoparticle ball film is formed at the water / air interface. Finally, the corresponding device film and wafer film can be obtained by using MEMS devices or wafers to scoop up the film.

[0052] In specific operations, the composition ratio of indium salt can be adjusted to control In 3+The doping content is used to adjust the sensitivity of the gas sensor. Specifically, the ratio of the number of indium and tin atoms is in the range of 1% to 7%. Furthermore, the ratio of the number of indium and tin atoms is preferably in the range of 3% to 5%, for example, 4%.

[0053] Taking In(NO3)3 as indium salt and SnCl4 as tin salt as examples, the following compares the sensor performance under several different ratios of indium and tin atoms.

[0054] Example 1

[0055] (1) 0.008 g In(NO3)3, 0.8 g SnCl4, 0.8 ml 35% hydrochloric acid, 50 ml ethanol and 5 ml deionized water were mixed and stirred to form a uniform mixed solution;

[0056] (2) The mixed solution obtained in (1) was magnetically stirred for 6 h, then transferred to a reaction vessel, and then subjected to a hydrothermal reaction at 200 °C for 12 h;

[0057] (3) The hydrothermal product obtained in (2) is centrifuged, washed and dried, and annealed at 500°C for 2 h in an air atmosphere. The obtained sample is a 1% In-SnO2 nanomaterial, where 1% means that the mass ratio of indium salt to tin salt is 1%, and the corresponding ratio of the number of indium and tin atoms is 1.3%.

[0058] Example 2

[0059] (1) 0.024 g In(NO3)3, 0.8 g SnCl4, 0.8 ml 35% hydrochloric acid, 50 ml ethanol and 5 ml deionized water were mixed and stirred to form a uniform mixed solution;

[0060] (2) The mixed solution obtained in (1) was magnetically stirred for 6 h, then transferred to a reaction vessel, and then subjected to a hydrothermal reaction at 200 °C for 12 h;

[0061] (3) The hydrothermal product obtained in (2) was centrifuged, washed and dried, and annealed at 500°C for 2 hours in an air atmosphere. The obtained sample was a 3% In-SnO2 nanomaterial, and the atomic ratio of indium to tin was 4%.

[0062] Example 3

[0063] (1) 0.040 g In(NO3)3, 0.8 g SnCl4, 0.8 ml 35% hydrochloric acid, 50 ml ethanol and 5 ml deionized water were mixed and stirred to form a uniform mixed solution;

[0064] (2) The mixed solution obtained in (1) was magnetically stirred for 6 h, then transferred to a reaction vessel, and then subjected to a hydrothermal reaction at 200 °C for 12 h;

[0065] (3) The hydrothermal product obtained in (2) is centrifuged, washed and dried, and annealed at 500° C. for 2 h in an air atmosphere. The obtained sample is a 5% In-SnO2 nanomaterial, and the atomic ratio of indium to tin is 6.5%.

[0066] Example 4

[0067] (1) 0.024 g In(NO3)3, 0.8 g SnCl4, 0.8 ml 35% hydrochloric acid, 50 ml ethanol and 5 ml deionized water were mixed and stirred to form a uniform mixed solution;

[0068] (2) The mixed solution obtained in (1) was magnetically stirred for 6 h, then transferred to a reaction vessel, and then subjected to a hydrothermal reaction at 200 °C for 12 h;

[0069] (3) The hydrothermal product obtained in (2) is centrifuged, washed and dried, and then annealed at 500° C. for 2 h in an air atmosphere.

[0070] (4) 0.1 g of the sample obtained in step (3) was mixed evenly with 0.005 g of dichlorotetraamminepalladium, 0.1 g of sodium borohydride, and 10 ml of deionized water, and then centrifuged, washed, and dried.

[0071] (5) The sample obtained in step (4) is annealed at 300° C. in a hydrogen atmosphere to obtain a high-performance 3% In-SnO2 / Pd nanomaterial.

[0072] As shown in Figure 5(a), it is a gas response diagram of H2S at different temperatures when different nanomaterials are used as sensitive films. It can be seen from the figure that the response performance of the sensor using pure SnO2 nanomaterial as the sensitive film is the weakest. The response performance of the sensor using 3% In-SnO2 nanomaterial as the sensitive film is better than the response performance of the sensor using 1% In-SnO2 nanomaterial as the sensitive film, and better than the response performance of the sensor using 5% In-SnO2 nanomaterial as the sensitive film. After the 3% In-SnO2 nanomaterial is modified with palladium, the response performance of the sensor when it is used as the sensitive film is greatly improved, indicating that In 3+ The In-SnO2 / Pd nanomaterial doped and modified with palladium nanoparticles can greatly improve the performance of the sensor when used as a sensitive film.

[0073] The following table shows the comparative data of oxygen vacancy concentration and oxygen adsorption capacity of different nanomaterials. lat, O vac , O ads Represent lattice oxygen, oxygen vacancies and adsorbed oxygen, respectively. As can be seen from the table, the oxygen vacancy concentration and oxygen adsorption capacity of pure SnO2 nanomaterials are the weakest, 3% In-SnO2 nanomaterials are better than 1% In-SnO2 nanomaterials and 5% In-SnO2 nanomaterials, and 3% In-SnO2 / Pd nanomaterials are better than 3% In-SnO2 nanomaterials, which can also explain the differences in the response performance of different sensors in Figure 5(a).

[0074]

[0075] As shown in Figure 5(b), it is a comparison of gas responses when different nanomaterials are used as sensitive films. It can be seen that when In-SnO2 / Pd nanomaterial is used as the sensitive film, its overall gas response performance is the best.

[0076] As shown in Figure 5(c), it is a graph showing the relationship between gas response and concentration when In-SnO2 / Pd nanomaterial is used as the sensitive film. It can be seen that the gas response degree of the sensitive film increases with the increase of gas concentration, indicating that the sensor can detect changes in gas concentration.

[0077] As shown in Figure 6(a), it is a SEM image of an 8-inch wafer-level film made using n-SnO2 / Pd nanomaterials as a sensitive film. As shown in Figure 6(b), it is a consistency test of the dynamic response of four sensors in four areas on an 8-inch wafer to H2S gas at 280°C. It can be seen from the figure that the gas dynamic response of sensors in different areas has good consistency.

[0078] Accordingly, the present invention also relates to a method for synthesizing a high-performance In-SnO2 / Pd sensitive film for a MEMS gas sensor, wherein the sensitive film is made of nanoparticle balls In-SnO2 / Pd, wherein the nanoparticle balls In-SnO2 / Pd are In 3+ Doped and Pd-modified tin dioxide nanoparticles. Specifically, the sensitive film can be prepared by the preparation method described above.

[0079] Correspondingly, the present invention also relates to a MEMS gas sensor, which includes the sensitive film for MEMS gas sensing introduced above. Specifically, the gas sensor includes a MEMS chip and a sensitive film covering the surface of the MEMS chip. The target gas in the environment will undergo an oxidation reaction with the sensitive film to cause the resistance of the sensitive film to change. The MEMS chip detects the target gas by detecting the resistance of the sensitive film.

[0080] The technical features of the above-mentioned embodiments can be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. It should be noted that "in one embodiment", "for example", "for example", etc. of the present invention are intended to illustrate the present invention, rather than to limit the present invention.

[0081] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for synthesizing a high-performance In-SnO2 / Pd sensitive film for a MEMS gas sensor, characterized in that: include: Step S1: firstly, indium salt, tin salt, hydrochloric acid, ethanol and deionized water are mixed and stirred uniformly, and then a hydrothermal reaction is carried out. Then, the product of the hydrothermal reaction is centrifuged, washed and dried, and then a first annealing treatment is carried out in an air atmosphere to obtain In 3+ Doped tin dioxide nanoparticle spheres In-SnO2, wherein the nanoparticle spheres In-SnO2 have a hollow structure; Step S2: modifying the nanoparticles In-SnO2 with palladium nanoparticles by a solution method, centrifuging, washing and drying, and then performing a second annealing treatment in a hydrogen atmosphere to obtain In 3+ Doped and Pd-modified tin dioxide nanoparticle spheres In-SnO2 / Pd; Step S3: making the nanoparticle balls In-SnO2 / Pd into the sensitive film.

2. The method for synthesizing a high-performance In-SnO2 / Pd sensitive thin film for a MEMS gas sensor according to claim 1, characterized in that: In step S1, the mixing ratio of the tin salt, hydrochloric acid, ethanol and deionized water satisfies: (2.0~2.4)mmol tin atom: (0.6~1.0)ml 35% hydrochloric acid: (48~52)ml ethanol: (4~6)ml deionized water.

3. The method for synthesizing a high-performance In-SnO2 / Pd sensitive thin film for a MEMS gas sensor according to claim 1, characterized in that: In step S1, the indium salt includes one or more of indium nitrate, indium chloride, and indium acetate, and the tin salt includes one or more of tin nitrate, tin chloride, stannous chloride, and tin acetate.

4. The method for synthesizing a high-performance In-SnO2 / Pd sensitive thin film for a MEMS gas sensor according to claim 1, characterized in that: In step S1, the ratio of indium salt to tin salt satisfies that the ratio of the number of indium atoms to that of tin atoms is in the range of 1% to 7%.

5. The method for synthesizing a high-performance In-SnO2 / Pd sensitive thin film for a MEMS gas sensor according to claim 4, characterized in that: In step S1, the ratio of indium salt to tin salt satisfies that the ratio of the number of indium atoms to that of tin atoms is in the range of 3% to 5%.

6. The method for synthesizing a high-performance In-SnO2 / Pd sensitive thin film for a MEMS gas sensor according to claim 1, characterized in that: In step S2, the step of modifying the nanoparticle spheres with In-SnO2 using a solution method comprises: The nanoparticle ball In-SnO2, palladium salt, palladium salt reducing agent and deionized water are mixed evenly. The palladium salt reducing agent is used to reduce the high-valent palladium ions in the palladium salt into a single palladium substance and embed it in the nanoparticle ball In-SnO2. In the nanoparticle ball In-SnO2 / Pd, the ratio of the number of palladium and tin atoms ranges from 0.1% to 5%.

7. The method for synthesizing a high-performance In-SnO2 / Pd sensitive thin film for a MEMS gas sensor according to claim 1, characterized in that: The annealing temperature of the first annealing treatment is 450°C to 550°C; the annealing temperature of the second annealing treatment is 250°C to 350°C.

8. The method for synthesizing a high-performance In-SnO2 / Pd sensitive thin film for a MEMS gas sensor according to claim 1, characterized in that: In step S3, the step of making the nanoparticle balls In-SnO2 / Pd into the sensitive film comprises: The nano particle sphere In-SnO2 / Pd is made into the sensitive film through a gas / liquid interface self-assembly method.

9. A high-performance In-SnO2 / Pd sensitive film for MEMS gas sensor, characterized in that: The sensitive film is made of nanoparticle balls In-SnO2 / Pd, and the nanoparticle balls In-SnO2 / Pd are In 3+ Doped and Pd-modified SnO2 nanoparticle spheres.

10. A MEMS gas sensor, characterized in that: It comprises the high-performance In-SnO2 / Pd sensitive film as described in claim 9.

Citation Information

Cited By

  • Preparation method and application of a gas-sensitive palladium-tin oxide target

    CN122916647A